2020
DOI: 10.1123/jsr.2018-0276
|View full text |Cite
|
Sign up to set email alerts
|

No Relationship Between Preoperative and Early Postoperative Strength After ACL Reconstruction

Abstract: Context: All rehabilitative programs before anterior cruciate ligament (ACL) reconstructive surgery, which are focused on recovery of proprioception and muscular strength, are defined as prehabilitation. While it has shown that prehabilitation positively affects the overall outcome after ACL reconstruction, it is still controversial whether preoperatively enhancing quadriceps strength has some beneficial effect on postoperative strength, mainly during the first period. Objective: To determine whether there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The follow-up duration of the supportive studies ranged from 3 months to 2 years. On the contrary, Mariani PP et al [26] (moderate quality) reported that there was no association between pre-operative and post-operative QSI. In the study, quadriceps strength was measured by MVIC test early after injury, and at 2 and 3 months after surgery.…”
Section: Post-operative Quadriceps Strengthmentioning
confidence: 96%
See 4 more Smart Citations
“…The follow-up duration of the supportive studies ranged from 3 months to 2 years. On the contrary, Mariani PP et al [26] (moderate quality) reported that there was no association between pre-operative and post-operative QSI. In the study, quadriceps strength was measured by MVIC test early after injury, and at 2 and 3 months after surgery.…”
Section: Post-operative Quadriceps Strengthmentioning
confidence: 96%
“…The score of quality assessment ranged from 44-78, with a mean of 62 ± 10.4. There were nine studies of moderate quality [11][12][13][14][22][23][24][25][26]] and 3 studies were low quality [27][28][29][30][31][32][33][34][35][36][37][38][39]. The scores of each individual study are shown in ▶Table 1.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations